Pemodelan Penjualan Produk Herbal Menggunakan Metode Monte Carlo - Elvin Syahrin; Julius Santony; Jufriadif Na’am (Jurnal KomtekInfo, 2018)
Sales are a source of life for a company. Predicting the number of sales is important in analyzing the development of sales. Analysis of sales development is an important factor in increasing sales. Using the Monte Carlo method can predict the accuracy of the data items in the company. The results of this study on data processing in 2016 until 2017 have an accuracy of 97%. So this research is very precise in predicting sales for the future